2013
DOI: 10.18553/jmcp.2013.19.7.549
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Educational Outreach Program on Prescribing Potential Drug-Drug Interactions

Abstract: BACKGROUND: The topic of improving prescribing practices is a major focus of many national initiatives, not only to enhance the quality of health care but also to reduce medical care costs. Educational outreach (also known as academic detailing) is a type of postgraduate education where trained clinical consultants meet face-to-face with prescribers to provide one-on-one information. Ideally, such visits promote evidence-based knowledge, create trusting relationships, and induce practice change, particularly w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Despite enhanced medication appropriateness and the intervention with medication review and DDI check, mean number of severe DDIs increased. Previous studies found similar results [53, 54]. This may be related to multi-morbidity and polypharmacy which are associated with an elevated risk of DDIs [52, 55].…”
Section: Discussionsupporting
confidence: 73%
“…Despite enhanced medication appropriateness and the intervention with medication review and DDI check, mean number of severe DDIs increased. Previous studies found similar results [53, 54]. This may be related to multi-morbidity and polypharmacy which are associated with an elevated risk of DDIs [52, 55].…”
Section: Discussionsupporting
confidence: 73%
“…Demonstrating the effectiveness of interventions to improve the appropriate use of polypharmacy in older patients is hardly achievable in clinical practice, especially when performing educational meetings/workshops, which can have small or even unproven benefit . In fact, the latest Cochrane review concluded that ‘ It is unclear whether interventions to improve appropriate polypharmacy , such as pharmaceutical care , resulted in clinically significant improvement ’ .…”
Section: Discussionmentioning
confidence: 99%
“…In the recent past, administrative databases have been largely used to estimate the prevalence of DDIs as well as to determine possible predictors/determinants of DDI occurrence, especially in elderly under poly‐therapy . However, only a limited number of studies have attempted to assess the impact of educational campaigns to improve appropriateness of clinicians' prescriptions, with a non‐significant effect of educational outreach programmes on the prescribing rate of potential DDIs .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, evidence regarding treatment efficacy and DDIs is evolving on a daily basis, and therefore, updated resources/information must be available. As a result, the issue of improving prescribing practices is a major focus of many national initiatives, not only to enhance the quality of healthcare services, but also to reduce medication errors and medical care costs [15].…”
Section: Discussionmentioning
confidence: 99%